United Kingdom multicentre clinical trial of somatrem. Issue 8 (August 1987) - Milner, R D; Barnes, N D; Buckler, J M; Carson, D J; Hadden, D R; Hughes, I A; Johnston, D I; Parkin, J M; Price, D A; Rayner, P H
Abstract : In a multicentre clinical trial 54 children aged 4.0 to 17.3 years, who had growth hormone deficiency that had not previously been treated, were given biosynthetic methionyl growth hormone (somatrem) 4 units three times a week by subcutaneous or intramuscular injection for one year. Height was measured every three months for at least one year before and during treatment. Forty two patients responded to treatment with an increase in growth of greater than 1.5 cm/year. The remaining 12 who grew more slowly were less obviously short and had a higher pretreatment growth than those who responded. The three who responded and the one who did not had undergone therapeutic spinal irradiation before starting the drug. If a whole year's pretreatment growth rate of less than 5 cm/year had been used as a diagnostic criterion the prediction of those who responded would have slightly improved. About two thirds of the patients developed antibodies against growth hormone and Escherichia coli protein; these were, however, of low and fluctuating titre and binding capacity, and did not influence the response to treatment. No adverse side effects were encountered. We conclude that somatrem is a safe and effective alternative to pituitary growth hormone.